Asymmetric signatures of warps in edge-on disks - Kimmig, Carolin; Villenave, Marion (Astronomy and astrophysics, 2025)
Context. Protoplanetary disks observed edge-on commonly show asymmetries that can be caused by shadows cast from a misaligned inner region or warp. With the growing amount of these observations, methods to constrain warp parameters are urgently needed. Aims. For this work, we investigated observational signatures of warps in edge-on disks with the aim of finding limits on the observability of warps. Methods. We performed radiative transfer simulations in scattered light (near-/mid-infrared) of edge-on disks containing warps of different amplitudes and varying sizes of the misaligned inner region. We analyzed the effect of these parameters on observations at λ = 0.8 μm, but also compared models for specific parameters at wavelengths up to λ = 21 μm. In all models, we quantified the asymmetry by fitting the two nebulae corresponding to the disk surfaces individually. Results. We find that under optimal conditions, an asymmetry due to slight warps can be visible. The visibility depends on the viewing angle, as warped disks are not axisymmetric. For optimal azimuthal orientation, misalignments between inner and outer disk regimes as low as 2° can lead to significant asymmetries. On the other hand, we find that larger misalignments of about 10° are needed in order to observe a change in the brightest nebula as a function of wavelength, which is observed in a few protoplanetary disks. To link our results to observations, we investigate the potential misalignments between the inner and outer disk of edge-on systems showing asymmetries. We compare the jet geometry, which presumably traces the very inner regions of the disk, to the outer disk orientation of four systems and find that a misalignment of a few degrees could be consistent with the data, such that warped disks could explain the apparent lateral asymmetries. Conclusions. There are many factors that can influence the appearance of the shadows and asymmetries in warped disks. Although it is still challenging to infer exact warp parameters from observations, this work presents a promising step toward better constraints.